USING FILM TO ADDRESS THE AFFECTIVE DOMAIN OF LEARNING RELATED TO THE NURSING EDUCATION OF CARING FOR THE LGBTQ+ PATIENT - Wilkerson , Sydney (East Carolina University, 2023)
Abstract Background: Appropriate and adequate care for LGBTQ+ patients and other special populations by nurses begins with receiving proper education and a strong background in personalized patient care. Due to the lack of preparedness felt by some new graduate nurses, there is even more emphasis on the need to improve this understanding and the educational resources used to prepare for the care of some patients. Understanding what academic resources are best suited to reach an adequate knowledge for care and providing this care with emotional intelligence is important and vital to the role that nurses play in patient care of special populations such as the LGBTQ+ community. Methods: A literature search was conducted by utilizing online databases that included PubMed, and a significant impact in research resulting from Elsevier and Evolve. Study quality was assessed prior to inclusion to provide the best quantitative and qualitative research available that was deemed relevant to this research conduction. Findings from these studies were analyzed and resulted in a synthesis of conclusions from each resource to provide an integrated literature review regarding the topic. Results: Twelve studies were included in this review from over a thousand that were retrieved in the initial search. It was identified which resources supported the research of this topic and which resources showed the gap in this research that should be further conducted. This research showed that overall, there is very limited resources exploring the effects of using film in nursing education and which academic resources provide the most successful emotional connection regarding certain topics. Conclusion: After reviewing the literature, it is evident that limited research has been done on the most effective teaching pedagogy for nursing education and should be further explored. However, in the literature that has been provided on teaching through film and documentaries in nursing curriculum, it has been proven to be extremely effective in the knowledge base and emotional connection to specific patient populations that is provided. The success in certain areas of nursing education through alternative formats needs to be further explored to determine the overall effectiveness compared to traditional teaching platforms in the same curriculum areas.
Keywords: Affective Domain LGBTQ+ Patients Nursing Education